REVIVING THE VERNACULAR: A SOCIO-CULTURAL AND ARCHITECTURAL STUDY OF MARATHA RESIDENCES IN MAHARASHTRA (International Journal of Food and Nutritional Sciences, 2023)
This study explores the architectural and social-cultural values of the Maratha residential buildings specially, Wadas in Maharashtra. With the amalgamation of ethnographic case studies, architectural records, and oral histories of five heritage houses in Pune, Satara, Kolhapur, Nashik and Wai, the research investigates the ways traditional residence reflects the social stratification, the ritual and the ecological wisdom. According to key findings, it has been established that 100 percent of the houses are based on a courtyard centric pattern and 80 percent of them still retain the original facilities like lime plaster and teak wood. The geographical mapping reveals that 60 percent of ritual areas such as the Devghar and Tulsi Vrindavan are being underutilized or modified, which means cultural disengagement. The interviews of 15 residents highlighted the breakdown of symbolic practices transmission carried on through the generations and memory breakdown. The conservation problems entail mismatch of material replacement (added in 4 of 5 sites) and deprivation of legal defense. Nevertheless, local consciousness is very high, and 70% of interviewees are willing to be restored in case they are aided at an institutional level. The study identifies a strong necessity to create the culturally sensitive and participatory preservation strategies that cannot be limited to the statuesque conservation of architecture. It ends up by promoting active revival strategies that do not interfere with tangible or intangible heritage.